1984
DOI: 10.1002/hep.1840040602
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR Antigens in HBsAg-Positive Chronic Active Liver Disease with and without Associated Delta Infection

Abstract: The A, B, C and DR locus specificities of the human leukocyte antigens system (HLA) were determined in 45 delta-positive and 44 delta-negative Italian patients, all with HBsAg-positive chronic active liver disease; controls were 526 healthy Italian blood donors matched for age, sex and geographical origin. HLA-A, B, C gene frequencies were not significantly changed. In delta-positive patients, the frequencies of the DR locus specificities were: DR2, 37.8%; DR3, 20%; DR4, 11.1%. In the delta-negative patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…11,12 Previous studies have shown that human leukocyte antigen polymorphisms may be associated with the hepatitis activity of chronic HBV carriers. [13][14][15] However, the determination of whether other host immunogenetic factors also influence the severity of hepatitis flares and clinical outcomes of HBV carriers deserves additional studies.…”
mentioning
confidence: 99%
“…11,12 Previous studies have shown that human leukocyte antigen polymorphisms may be associated with the hepatitis activity of chronic HBV carriers. [13][14][15] However, the determination of whether other host immunogenetic factors also influence the severity of hepatitis flares and clinical outcomes of HBV carriers deserves additional studies.…”
mentioning
confidence: 99%
“…In four cases cirrhosis of the liver could be established unequivocally. In three of them (patients [1][2][3] this could also be confirmed at post mortem investigation. Two of the cirrhotic patients were girls.…”
Section: Resultsmentioning
confidence: 61%
“…The development of certain forms of chronic active liver disease seems to be associated with certain H L A phenotypes (2,3). As the genes for a,AT are localized on the same chromosome as the immunoglobulin heavy chains (4) the possibility arises that the liver damage in a,AT deficiency could be immunologically mediated.…”
mentioning
confidence: 99%
“…Were an association between certain HLA antigens and aI-AID liver disease to exist, one would have expected an enrichment of these HLA antigens in a population of individuals with liver disease sufficiently severe as to be referred for liver transplantation. Such would appear to be the case for other liver disease like autoimmune chronic active hepatitis, sclerosing cholangitis, and chronic HBV-related liver disease (15)(16)(17)(18)(19). Despite this bias in the accrual of subjects for this study, no association between any HLA antigens and particularly DR3 was found in either children or adults or both groups combined having aI-AID liver disease confirmed by quantitation of the serum aI-AT level, isoelectric focusing for phenotype analysis, and family studies of the probands as well as having a need for OLTx.…”
Section: Discussionmentioning
confidence: 96%